Sclerosing Polycystic Adenosis of the Retromolar Pad Area: A Case Report. (3rd March 2014) - Mokhtari, Sepideh; Atarbashi Moghadam, Saede; Mirafsharieh, Abbas
Abstract : Sclerosing polycystic adenosis is a rare pathological lesion that affects salivary glands. The majority of cases involve the parotid and its occurrence in minor glands is exceedingly rare. Here, we report the first case of this lesion in the retromolar pad area and discuss its histological features and immunohistochemical reactivity with α SMA and Ki67 markers. A review of the literature on its immunohistochemical profile is also provided. Sclerosing polycystic adenosis has a diverse histomorphology and should be differentiated from other more important pathologic lesions.